2014
DOI: 10.1590/s1806-37132014000500009
|View full text |Cite
|
Sign up to set email alerts
|

Air stacking: effects on pulmonary function in patients with spinal muscular atrophy and in patients with congenital muscular dystrophy,

Abstract: OBJECTIVE: Respiratory complications are the main causes of morbidity and mortality in patients with neuromuscular disease (NMD). The objectives of this study were to determine the effects that routine daily home air-stacking maneuvers have on pulmonary function in patients with spinal muscular atrophy (SMA) and in patients with congenital muscular dystrophy (CMD), as well as to identify associations between spinal deformities and the effects of the maneuvers. METHODS: Eighteen NMD patients (ten with CMD and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 25 publications
3
46
0
2
Order By: Relevance
“…11,13,14,26 A recent study reported that air stacking can be learned by children with severe muscle weakness. 27 In 18 subjects affected by spinal muscular atrophy and congenital muscular dystrophy, air stacking was shown to be an effective airway clearance therapy. However, air stacking was more effective in the absence of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14,26 A recent study reported that air stacking can be learned by children with severe muscle weakness. 27 In 18 subjects affected by spinal muscular atrophy and congenital muscular dystrophy, air stacking was shown to be an effective airway clearance therapy. However, air stacking was more effective in the absence of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a recent study reported values < 270 L/min of PCF in a mixed group of 4 SMA II and 4 SMA III patients [42] and an improvement of this parameter after air stacking. Based on this report and on clinical observations expiratory aids should be Page 11 of 31 recommended in SMA III patients, particulary during acute illness.…”
Section: Cough Assistancementioning
confidence: 92%
“…Small, prospective observational studies of 3–6 months’ duration have reported conflicting outcomes. FVC and MIC did not change in 18 patients, but small gains in PCF (257.80 ± 84.31 pre vs 277.90 ± 90.24 L/min post) were observed . Whether this PCF change is clinically significant is unclear as normal PCF variability is not known.…”
Section: Evidence Of Efficacy During Clinical Stabilitymentioning
confidence: 90%